Factory farming - Miller, Debra A. (Detroit Greenhaven Press, 2010)
Contains essays that offer a variety of perspectives on the issue of factory farming, debating whether factory farming is economically beneficial, ethical, or harmful to human health or the environment, and considering the future of the industry.
ch. 4: What is the future of factory farming? -- Commercial agriculture will continue to play a role in agriculture policy / George McGovern and Marshall Matz -- Industrial agriculture must be carefully regulated in the future / Will Allen -- Industrial animal agriculture must transition to a more sustainable system / Pew Commission on Industrial Farm Animal Production -- The world must abandon the commodity approach to food / Greg Bowman -- Enlightened agriculture is the key to future farming and meat production / Colin Tudge.
99833
Keywords: Factory farms; Livestock farms; Farming; Livestock industry; Meat industry